Flaws in the design of the Examen Nacional para Aspirantes a Residencias Médicas produce inequity - Aldo Barajas-Ochoa; César Ramos-Remus; José Dionisio Castillo-Ortiz; José Yáñez; Zalathiel Barajas-Ochoa; Jorge Manuel Sánchez-González; Mauricio Hernández-Ávila; José Ángel Córdova-Villalobos; Lilia Patricia Bustamante-Montes (Instituto Nacional de Salud Pública, 2019)
Objective. To assess the assumption of 'equity' of Mexico's resident-selection assessment tool, the Examen Nacional para Aspirantes a Residencias Médicas (ENARM). Materials and methods. Official ENARM-2016 and -2017 databases were analyzed. Differences in the absolute number of correct answers (multivariable linear regression) and the number of applicants reaching their specialty minimum score (SMS) per test day (odds ratio [OR]) were calculated. Applicants affected by test-day inequity were estimated. Results. There were 36 114 applicants in 2016, and 38 380 in 2017. In 2016, day-2 applicants had significantly higher scores and more reached the SMS than on days 1-3-4 (OR 1.55), and 5 (OR 3.8); 3 565 non-passing applicants were affected by inequity (equivalent to 44.64% of those selected). In 2017, day-1 and -2 applicants had significantly higher scores and more reached the SMS than on days 3-4 (OR 1.85), and 5 (OR 4.04); 3,155 non-passing applicants were affected by inequity (37.2% of those selected). Conclusion. Analysis of official ENARM databases does not support the official attribution of equity, suggesting the test should be redesigned.